Combination taping technique versus ankle foot orthosis on improving gait parameters in spastic cerebral palsy: A controlled randomized study - Mohamed A. Abdel Ghafar; Osama R Abdelraouf; Amr A. Abdel-aziem; Gihan Samir Mousa; Ali O. Selim; Mariam E. Mohamed (Medical Journals Sweden, 2021)
Background: One of the important goals in the treatment of spastic cerebral palsy is to maintain efficient and effective walking in order to be independent in activities and participate in society.  Objective: To compare the efficacy of foot combination taping of kinesio tape and athletic tape vs ankle foot orthosis in correcting spatiotemporal gait parameters in children with spastic diplegia. Methods: Thirty-six children with spastic diplegia were randomly assigned into 3 groups; control, combination taping, and ankle foot orthosis groups. Children in the control group, in addition to those in both experimental groups, continued with conventional physical therapy, 1 h, 3 times per week for 4 weeks. Spatiotemporal gait parameters were assessed with the GAITRite system before and after the application of interventions. Results: There were significant increases in walking velocity, step length, stride length, right single support duration, and left single support duration of the ankle foot orthosis and combination taping groups compared with pre-intervention values. Moreover, the post--intervention values of the double support duration of the ankle foot orthosis and combination taping groups were significantly lower than pre-intervention values. There were no significant differences between the post-intervention values of the ankle foot orthosis and combination taping groups for all parameters. Conclusion: The results demonstrated that combination taping is an effective alternative technique to ankle foot orthosis to improve spatiotemporal parameters in children with spastic diplegic in combination with conventional physiotherapy.   Lay Abstract Children with cerebral palsy have abnormal patterns of walking secondary to spasticity, which can negatively affect their functional abilities and quality of life. Several therapeutic interventions are used, with the aim of improving gait quality in those children so that they become independent in functional activities and can participate in society. This study compared the effectiveness of ankle bracing with the application of a combination taping on gait parameters. The results showed that both interventions are equally effective. Combination taping might be considered a promising alterative to ankle joint bracing, as it is a more functional and less aggressive technique.